Effective and Sustainable Hydraulic Fracturing - Bunger, Andrew P.; McLennan, John; Jeffrey, Rob (IntechOpen, 2013)
This book comprises the proceedings for the International Conference for Effective and Sustainable Hydraulic Fracturing (HF2013) which was held 20-22 May 2013 in Brisbane, Australia. The conference goal was to advance hydraulic fracturing technology that is effective in its purpose and sustainable in its impacts on communities and environments by bringing together hydraulic fracturing experts not only from the petroleum industry, but also from other application areas of hydraulic fracturing such as mining and geothermal energy production. Topics include hydraulic fracturing of naturally fractured formations, well completions and fracture initiation, induced seismicity, experimental investigations, and coupled modelling. Beyond this mix of traditional hydraulic fracturing research topics, this book includes papers on applications in mining and also on regulations, risk, and communities.